Cognitive narrative psychotherapy: The hermeneutic construction of alternative meanings - Gonçalves, Óscar F. (1994)
Cognitive psychotherapies are experiencing dramatic conceptual changes. An increasing constructivist orientation along with a narrative model of the knowing processes is apparent in the most recent developments in cognitive theory. These changes demonstrate the need to develop new therapeutic methodologies able to effect deep changes in the knowing processes. This article tries to address these issues by presenting an illustration of a new therapeutic methodology hereafter referred to as cognitive narrative psychotherapy.